Biomass viability: An experimental study and the development of an empirical mathematical model for submerged membrane bioreactor. (August 2015) - Zuthi, M.F.R.; Ngo, H.H.; Guo, W.S.; Nghiem, L.D.; Hai, F.I.; Xia, S.Q.; Zhang, Z.Q.; Li, J.X.
Highlights: Sustainable operation of MBR greatly depends on biomass viability. Among biomass parameters, EPS has highest correlation with biomass viability. Proposed models correlate SOUR with characteristic biomass parameters. Mathematical model simulations agree well with the experimental results. Abstract: This study investigates the influence of key biomass parameters on specific oxygen uptake rate (SOUR) in a sponge submerged membrane bioreactor (SSMBR) to develop mathematical models of biomass viability. Extra-cellular polymeric substances (EPS) were considered as a lumped parameter of bound EPS (bEPS) and soluble microbial products (SMP). Statistical analyses of experimental results indicate that the bEPS, SMP, mixed liquor suspended solids and volatile suspended solids (MLSS and MLVSS) have functional relationships with SOUR and their relative influence on SOUR was in the order of EPS > bEPS > SMP > MLVSS/MLSS. Based on correlations among biomass parameters and SOUR, two independent empirical models of biomass viability were developed. The models were validated using results of the SSMBR. However, further validation of the models for different operating conditions is suggested.